Kingdom of Swaziland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
The current high Southern African Customs Unions revenues should be used to implement fiscal measures to secure fiscal sustainability and support economic growth. The government should formulate a financial sector strategy that addresses Swaziland's twin challenges of enhancing financial development and ensuring financial stability. Compounding the threat to exports of sugar and textiles is the looming issue of remaining competitive in a quickly changing global environment. The statistics on export and import, gross domestic product, assets and liabilities, and other such data have also been provided.